Tim Rogan. The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. - Dale, Gareth (The American Historical Review, 2019)
When the capitalist system hits the rocks and neoclassical economics loses its aura, alternative traditions invite attention. Tim Rogan’s The Moral Economists i
History
Keywords: The Moral Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson; and the Critique of Capitalism (book); book review; capitalism

The Double Movement Ten Years After the Fall of Lehman Brothers - Vidal, Gregorio; Marshall, Wesley C. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Ten years after the collapse of Lehman Brothers and the sharpest moments of panic within the global—and particularly the United States banking system—a somewhat strange dynamic has appeared. While the principal agents behind the crisis have collapsed their own institutions, the markets that they dominated, and even provoked what has been called the third crisis of economic theory, their political power has not waned. This theme has been well addressed by some academics such as Philip Mirowski (2013), while it has flummoxed others. In this article, we will argue that Karl Polanyi's theory of the "double movement" offers a coherent framework that is able to account for the history of the last ten years. Polanyi argues that different groups and members of society seek protection from the market, and that this search for protection has been the driving force between historical change. Polanyi does not ignore class; rather, he argues that different social classes can protect themselves in more or less effective ways. We argue that during the last ten years, the interests of globalized financial capital have been able to protect themselves with utmost effectiveness, while all other classes have been trammeled, often not even recognizing how or why actions are taken against the general interest.
Economics; History
Keywords: Lehman Brothers; capital market; double movement; financial crisis; financial markets; securities; stock exchanges; stocks (finance)

La società di mercato e le sue trasformazioni. Attualità di Karl Polanyi - Cangiani, Michele (Itinerari di ricerca storica, 2019)
ItIl neoliberalismo è sorto dall'esigenza di superare la crisi degli anni Settanta del secolo scorso, ma ha portato a una nuova crisi, da molti detta "sistemica". Siamo quindi sollecitati a riflettere sulle caratteristiche fondamentali del nostro sistema sociale e sulla sua storia. A questo fine, l'opera di Karl Polanyi fornisce preziose indicazioni. In essa, da una parte, la società di mercatocapitalistica viene definita in generale, nella sua specificità, mediante una comparazione a vasto raggio con le società precedenti. D'altra parte, viene analizzata la "trasformazione" di tale società da un assetto istituzionale all'altro, attraverso un periodo di crisi e di conflitto sociale. Poiché, tuttavia, le ragioni profonde della crisi permangono nel nuovo assetto insieme con le caratteristiche più generali del sistema sociale, la crisi tende a ripresentarsi, insieme all'esigenza di una nuova trasformazione istituzionale. Questo articolo intende mostrare che tale tesi è perlomeno implicita negli scritti di Polanyi e che quindi non solo la sua teoria della società di mercato in generale, ma anche le sue analisi delle vicende della "grande trasformazione" fra le due guerre mondiali possono essere utili per comprendere gli sviluppi ulteriori della nostra società fino alla situazione attuale.EnNeoliberalism arose from the need to overcome the crisis of the 1970s, but led to a new "systemic" crisis. We are therefore urged to reflect on the fundamental characteristics of our social system and its history. To this end, Karl Polanyi's work provides valuable suggestions. In it, on the one hand, the capitalist market society is defined in general, in its specificity, through a widerange comparison with previous societies. On the other hand, the "transformation" of that society is analyzed, from one institutional setup to another, through periods of crisis and social conflict. Since the deep reasons of the crisis remain in the new set-up, together with the more general characteristics of the social system, the crisis tends to recur, together with the need for a new institutional transformation. The present paper intends to show that this thesis is, at least, implicit in Polanyi's writings; therefore, not only his theory of the market society in general, but also his analysis of the events of the "great transformation" between the two world wars can be useful in understanding further developments of our society up to the current situation.
History
Keywords: capitalism; capitalismo; crisi; crisis; transformation; trasformazione

A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
History; Religious Studies
Keywords: Great Transformation; The (Book); KING; Martin Luther; Poor People's Campaign; TRUMP; Donald; embeddedness

In the market for humane rights - Inglis, Fred (Times Higher Education, 2018)
History; Education
Keywords: Human rights; Moral Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); Rogan; Tim; austerity (economics); book review; cultural history; nonfiction

La Contribución Del Análisis Institucional a Las Ciencias Sociales! - Polanyi, Karl (Revista de Economía Institucional, 2018)
El artículo presenta un discurso del autor en la Conferencia de la Sociedad de Postgrado de Economía de la Universidad de Colombia, Nueva York, en 1950, acerca del análisis institucional a las ciencias sociales. Comenta sobre la relación entre tales ramas de las ciencias sociales como la historia, la economía y la antropología. ENG: The article presents a speech by the author at the Conference of the Graduate Society of Economics of the University of Colombia, New York, in 1950, about the institutional analysis of the social sciences. Comment on the relationship between such branches of the social sciences such as history, economics and anthropology
History; Anthropology; Economics
Keywords: For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; anthropology; anthropology & history; economics; ethnohistory; history & economics; original work; social science research; social sciences

The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism - Crook, Paul (Australian Journal of Politics & History, 2018)
The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. By Tim Rogan (Princeton and Oxford, Princeton University Press, 2017), pp.263 + viii. AU$48.82 (hb). Available in Australia through Footprint Books.
Political Science; History
Keywords: MORAL Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); POLANYI; Karl; 1886-1964 - political & social views; ROGAN; Tim; TAWNEY; R. H. (Richard Henry); 1880-1962; THOMPSON; E. P. (Edward Palmer); 1924-1993; book review; nonfiction; political attitudes

The Double Movement of the Landlord Class in Prewar Japan - Cohen, Mark (Journal of Japanese Studies, 2018)
The role of the landlord class in Japan's prewar economic and political development has been widely debated. Moving beyond conflicting arguments of landlords as semifeudal exploiters or as the linchpins of rural market development, more recent research has emphasized the nonmarket institutions, often inherited from the Tokugawa era, in which the contractual relations between landlords and tenants were embedded. However, this research has overemphasized the continuity of the rural economy. Rather than a smooth development, the historical trajectory of rural economic growth followed the "double movement" of capitalist development identified by the historian and economic anthropologist Karl Polanyi.
History; Japanese Studies
Keywords: Japan; Tokugawa Period; Japan; 1600-1868; capitalism; double movement; history; landlord-tenant relations

"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought – from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp – than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view – that is, to a radical approach to Polanyi's thought.
History; Economics
Keywords: Poor Law; WEBER; Max; 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Markets, Knowledge and Human Nature: Friedrich Hayek, Karl Polanyi and Twentieth-century Debates on Modern Social Order - Innset, Ola (European History Quarterly, 2017)
The article reads the works of Friedrich Hayek (1899-1992) and Karl Polanyi (1886-1964) in the light of their political commitments to neoliberalism and socialism respectively. It argues that both thinkers were inspired to explain history and recent events in line with these commitments in their 1944 publications, The Road to Serfdom and The Great Transformation. Furthermore, they both developed their most significant insights by attempting to counter perceived challenges from political projects to which they were opposed. Polanyi spent much of his life trying to disprove a liberal attack on socialism as out of touch with the realities of human nature, whereas it was in debates with socialists that Hayek developed a new theory of the epistemological functioning of markets, which then became foundational for the neoliberal project. Taking into account the high-stakes politics of Vienna in the interwar years is crucial for fully understanding the social theory of these two thinkers.
History
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; human behavior; knowledge; markets; neoliberalism; social order; socialist accounting; socialist calculation debate; totalitarianism

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
History; Sociology
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Karl Polanyi: A Life on the Left - Innset, Ola (European History Quarterly, 2017)
History
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); nonfiction

Karl Polanyi. Remettre l'économie à sa place - Behrent, Michael C. (Sciences humaines, 2016)
History

Karl Polanyi and the Reality of Society - Behrent, Michael C. (History and Theory, 2016)
This essay reconsiders Karl Polanyi's famous thesis about the “embeddedness” of the economy through an examination of two recent books: For a New West, a collection of previously unavailable essays by Polanyi, and Fred Block and Margaret R. Somers's The Power of Market Fundamentalism: Karl Polanyi's Critique. The guiding thread of this analysis is the claim that a constant in Polanyi's thought was his belief in what he called “the reality of society,” that is, that society exists as a social fact over and above the individuals that constitute it. The essay begins by tracing Polanyi's intellectual development, drawing primarily on the essays found in For a New West. Polanyi's quest to reconcile individual freedom with social solidarity led him first, in the years between the First and Second World Wars, to embrace liberal socialism, before his readings in anthropology persuaded him that traditional economies “embed” the economy in social relations and that the nineteenth-century liberal project of a “disembedded” economy (through the so-called free market) is a departure from this anthropological norm. The essay then examines and questions Block and Somers's claim that Polanyi maintained that the economy is always “already embedded,” arguing notably that Polanyi believed that the advent of market society entailed an economy that was actually disembedded from social relations, not merely one that was re-embedded in an alternative set of institutions.
History
Keywords: already embedded; anthropology; capitalism; embeddedness; liberalism; markets; reality of society; socialism; society

Embedding Capital: Political-Economic History, the United States, and the World - Kramer, Paul A. (Journal of the Gilded Age & Progressive Era, 2016)
The article examines U.S. political and economical history in the context of its impact as well as influence to world affairs. Topics discussed include the Marxist's historical approaches to analysis of capital as in Karl Polanyi's take on American capitalism, "primitive accumulation" with regimes of commodification and the "new history of capitalism" hype. Also mentioned were transnational expansion of humanitarianism, international education sponsorship and Andrew Carnegie's philanthropy.
History
Keywords: United States - politics & government - history; capital; capitalism; economics - United States - history; embeddedness; humanitarianism

Polanyi'nin Modern İktisatın İnsan Anlayışına Eleştirileri - Akan, Seriyye (Polanyi's Criticisms on Modern Economics' Conception of the Human Being., 2016)
Discipline of economics, who already assimilated the mathematical and technical tools as a base for the expression of theory is almost lost its identity as a social science. This process has become visible through some historical breakups. These breakups have scientific, social and economic faces. While the developments in natural sciences had led the economists to imitate physics - since it uses more certain methods as a science; the market society which established after the industrial revolution separated humans from the economic understanding of the past eras. Rationality, which indeed a philosophical concept, purified from its philosophical context and integrated to economics. On the other hand, the mainstream economics which accepts the maximisation of interest as one of the components of human nature prevailed the economics literature. The modern economics' conception of human had shaped via the steps which we briefly mentioned above. Karl Polanyi (1886-1964) had criticized the human conception of modern economics by using social anthropological methods. He had claimed that market system did not emerged spontaneously, the nature of human did not change throughout history, and primitive economics was totally different from today's market society since the economic relations were embedded in the other social relations. In this article, we tried to analyse Polanyi's criticisms on modern economics' human conception. For this reason, we firstly argued the term rationality in the economic context, since it would be a basis for our subject. Then we emphasized the thesis of "uncahged nature of human" which highlighted by Polanyi, discussions on primitive economies, and the market society which established parallel to the industrial revolution respectively. (English)
History; Anthropology
Keywords: holism; market society; primitive economies; rationality; social anthropology

Karl Polanyi in Vienna - Dale, Gareth (Historical Materialism, 2014)
In this article I discuss Polanyi's intellectual formation in early twentieth-century Budapest and in 1920s Vienna, focusing in particular upon his relationship to Guild Socialist and Marxist theory and to Austrian Social Democracy. It was a period in which Marxism was evolving rapidly, and Polanyi was too. In his twenties, he reacted forcefully against what he saw as the evolutionary and deterministic traits of Marxist philosophy. In his thirties, his relationship to Marxism underwent a 'double movement': his long-held doubts about Marxism crystallised into an forceful critique, swiftly followed by a sympathetic dialogue with the ideas and politics of Austro-Marxism, the 'Rousseauian' commitments of which were not unlike his own. I examine Polanyi's relationship with Marxism in each of these phases, and explore the affinities between Guild Socialism and Austro-Marxism. The final section introduces the distinctly un-Polanyian analysis of Austrian Social Democracy offered by Polanyi's wife, Ilona Duczynska.
Political Science; History
Keywords: 20th century; Austria; Austro; Austro-Marxist school; DUCZYNSKA; Ilona; Hungary; Marxism; Marxist philosophy; ROUSSEAU; Jean-Jacques; Vienna (Austria); biography; communism; determinism; functional theory; guild socialism; history; intellectual life; social democracy

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
History; Anthropology
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights

Polanyi's Magnum Opus ? Assessing the Application of the Counter-Movement in International Political Economy - Worth, Owen (International History Review, 2013)
The concept of the ‘counter-movement’ has had a significant impact within studies in International Political Economy (IPE). In the light of the credit crisis and the growth of growing resentment to the notion of the free market, the idea of the counter-movement has been utilised to understand social reaction to neoliberalism. This article argues that whilst the counter-movement has been used in unique and innovated ways, Karl Polanyi himself used the term largely to refer to a specific period in nineteenth-century British history. This article argues that whilst the counter-movement remains interesting, its application remains open to scrutiny. It questions whether the concept was indeed central to Polanyian economic thought and how much can be given to it in today's contemporary era of neoliberalism. It also suggests that by focusing merely on the counter-movement, Polanyian accounts within IPE are in danger of ignoring much of his wider critique of market economics.
Political Science; History
Keywords: capitalism; countermovement; economic policy; equilibrium (economics); foreign investments; free enterprise; international economic relations; international political economy; neoliberalism

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Geography; History
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
History; Economics
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

Le rendement et le butin. Regard écologique sur l'histoire du capitalisme, The Yield and the Booty. An Ecological Perspective on the History of Capitalism - Charbonnier, Pierre (Actuel Marx, 2013)
This article examines the history of globalized capitalism from the perspective of the relations to the environment which it helped to construct. It proposes a definition of globalized capitalism as a form of relation to nature. If philosophy has frequently postulated that modernity is characterized by the dissociation between the natural and the social, the history of the economic take-off of the states of Western Europe throws a singular light on this hypothesis. Combining a reading of Karl Polanyi and Kenneth Pomeranz, it can be argued that the logic of commodity always tends to render invisible the relations to the environment which define capitalism. The temporal and spatial lag between those populations which live the concrete experience of the industrial revolution and the enormous natural resources required for its appearance enable us to understand how it has been possible for the representation of the economy to become so radically dissociated from its natural metabolism.
History; Political Science
Keywords: globalized capitalism; nature and society; political thought

Nature and Power - Radkau, Joachim (Social Science History, 2013)
Nature and Power is to be understood not only as human power against nature but also as power by nature in the sense of Michel Foucault's biopouvoir (biopower) or Francis Bacon's "Naturae non imperator nisiparendo" (Only by obeying nature may we dominate nature). The fragile human attempts to get power over nature and by nature have a long history, reaching back over millennia until prehistoric times, and much of world history may be explained in part by the unstable relationship between humans and nature. The environmental approach offers afresh look at global history. The great change that has happened in modern times seems to have been described best by Karl Polanyi (1944) in his Great Transformation, which also refers to a revolution in the human relation to nature. There are primeval symbioses of humans and nature that are the basis of environmental history until modern time. A global history of the environment may be written for a long time along the three great commons of history: woodlands, water, and pasture. The dark tune of Garrett Hardin's (1968) "Tragedy of the Commons," to be sure, does not dominate the whole melody of environmental history. There is also a lot of historical evidence for Elinor Ostrom's rehabilitation of the commons. But it is better to be cautious with dogmatic theories and sweeping judgments. In modern times Hardin may be right, at least in this or that regard. Ostrom's concept applies only to local, not to global commons. The underlying philosophy of Nature and Power is neither optimism nor pessimism but possibilism.
History
Keywords: BACON; Francis; 1561-1626; FOUCAULT; Michel; 1926-1984; Nature & Power: A Global History of the Environment (Book); POLANYI; Karl; 1886-1964; RADKAU; Joachim; environmental history; environmentalism; nature and civilization

Cité et réciprocité, City and Reciprocity : The Role of Cultural Beliefs in the Roman Economy - Verboven, Koenraad (Annales. Histoire, Sciences Sociales, 2012)
La nouvelle économie institutionnelle est devenue populaire dans la recherche de l’économie antique depuis une dizaine d’années. Pourtant la notion de « croyances culturelles », qui joue un rôle central dans l’œuvre de Douglass North et dans les analyses du changement institutionnel par Avner Greif, a été largement ignorée. J’affirme qu’une approche néo-institutionnelle qui utilise cette notion de « croyances culturelles » offre une meilleure voie pour comprendre l’influence des idéologies et des valeurs morales sur l’économie antique que le modèle de Moses Finley. Des croyances culturelles ne sont pas des contraintes déterministes sur le comportement humain, mais elles aident à orienter les prises de décision et permettent d’anticiper les (ré) actions des autres. J’étudie deux ensembles de normes et de valeurs qui, dans la culture romaine, ont profondément marqué le cadre institutionnel de l’économie. L’un était centré sur la réciprocité. Ses normes et valeurs ont permis de construire et de maintenir des réseaux sociaux au-delà du groupe de la familia étendue avec ses affranchis. Elles étaient à la base du développement de la loi des obligations et de la représentation. L’autre se fondait sur la cité. Il a formé la culture politique en créant des droits et des obligations personnelles et en imposant des demandes légitimes aux élites politiques de défendre ceux-ci et de garantir et de stimuler des intérêts privés et communs. Le droit romain et la justice étaient ses résultats les plus importants. Idéologiquement, l’Empire romain se présentait comme une méta-cité qui incorporait les communautés locales qui, à leur tour, étaient graduellement transformées sur le modèle de la cité. Ces deux ensembles de croyances culturelles ont baissé les coûts de transactions, mais ils n’ont jamais menacé la prééminence de l’aristocratie locale et impériale. Vers la fin du IIe siècle de notre ère, les cités locales se sont affaiblies tandis que l’administration impériale se renforçait. Les aristocraties locales et régionales se sont tournées vers la bureaucratie et l’armée impériales pour maintenir leur rang social, leur influence et leur pouvoir. L’idéologie de la cité comme principe dominant de la culture politique devenait soumise à celle de l’empereur sacral, garant de la justice et de l’ordre divins. EN: New Institutional Economics have become popular in ancient economic history research the past decade. However, the notion of “cultural beliefs” that plays a central role in Douglass North’s recent work and in Avner Greif’s analysis of institutional change, has been largely ignored. I argue that a neo-institutional “cultural beliefs approach” offers a better way to understand the influence of ideology and moral values on the ancient economy than the Finley model does. Cultural beliefs are no deterministic constraints on human behavior but help to orient decision making and allow anticipating the (re)actions of others. I explore two key sets of norms and values in Roman culture that profoundly marked the economy’s institutional framework. One centered on reciprocity. Its norms and values supported social networks beyond the confines of the familia-freedmen group and underlay the development of contract and agency law. Another set rested on citizenship. It shaped political culture by creating individual rights and obligations and laying legitimate claims on political elites to enforce these and to take action to secure and stimulate private and common interests. Roman law and the distribution of justice was its prime off-spring. Ideologically the Roman Empire presented itself as a meta-city that incorporated local communities which in turn were gradually transformed to fit the civitas model. Both belief sets lowered transaction costs, but they never threatened the preeminent position of local and imperial aristocracies. Towards the end of the second century CE local communities became weaker while the imperial administration grew stronger. This caused local and regional aristocracies to turn to the imperial court and army for status, influence and power. The ideology of citizenship as the guiding principle of political culture gave way to that of the sacred emperor who guaranteed divine justice and order.
History
Keywords: Roman Empire; ancient economic history; ancient economies; cultural beliefs approach; institutional economics

Adam Smith's Green Thumb and Malthus's Three Horsemen: Cautionary Tales from Classical Political Economy - Dale, Gareth (Journal of Economic Issues (Taylor & Francis Ltd), 2012)
This essay identifies a contradiction between the flourishing interest in the environmental economics of the classical period and a lack of critical parsing of the works of its leading representatives. Its focus is the work of Adam Smith and Thomas Malthus. It offers a critical analysis of their contribution to environmental thought and surveys the work of their contemporary devotees. It scrutinizes Smith's contribution to what Karl Polanyi termed the "economistic fallacy," as well as his defenses of class hierarchy, the "growth imperative" and consumerism. It subjects to critical appraisal Malthus's enthusiasm for private property and the market system, and his opposition to market regulation. While Malthus's principal attraction to ecological economists lies in his having allegedly broadened the scope of economics, and in his narrative of scarcity, this article shows that he, in fact, narrowed the scope of the discipline and conceptualized scarcity in a reified and pseudo-scientific way.
Political Science; History
Keywords: MALTHUS; T. R.; SMITH; Adam; 1723-1790; classical political economy; consumerism; ecological economics; economistic fallacy; environmental economics; environmental policy; growth imperative; natural capital; scarcity

Conventions, the Great Transformation and Actor Network Theory - De Munck, Bert (Konventionen, die große Transformation und Actor Network Theory., 2012)
This article proceeds from the field of tension between the synchronical approach of the economics of convention and the diachronical approach of economic anthropology (in the tradition of Karl Polanyi). It is argued that the economics of convention remain problematic to historians in that they fail to capture the long term transformations traditionally referred to as the emergence of modernity and the coming about of homo economicus. As a possible solution, the use of concepts and insights from Actor Network Theory is proposed. While this cluster of theories enables an historical perspective without considering modernity as a natural process, it confronts changing relationships between subjects, objects and cultural systems of meaning head on.
History
Keywords: CALLON; Michel; actor-network theory; conventions; economic anthropology; economic aspects; history; manners & customs; modernity; performativity

Twentieth-Century Jewish Émigrés and Medieval European Economic History - Mell, Julie (Religions, 2012)
This essay discusses the intellectual contributions of five Jewish émigrés to the study of European economic history. In the midst of the war years, these intellectuals reconceptualized premodern European economic history and established the predominant postwar paradigms. The émigrés form three distinct groups defined by Jewish identity and by professional identity. The first two (Guido Kisch and Toni Oelsner) identified as Jews and worked as Jewish historians. The second two (Michal Postan and Robert Lopez) identified as Jews, but worked as European historians. The last (Karl Polanyi) was Jewish only by origin, identified as a Christian socialist, and worked first as an economic journalist, then in worker's education and late in life as a professor of economics. All five dealt with the origin of European capitalism, but in different veins: Kisch celebrated and Oelsner contested a hegemonic academic discourse that linked the birth of capitalism to Jews. Postan and Lopez contested the flip-side of this discourse, the presumption that medieval Europe was pre-capitalist par excellence. In doing so, they helped construct the current paradigm of a high medieval commercial revolution. Polanyi contested historical narratives that described the Free Market as the natural growth of economic life. This essay explores the grounding of these paradigms in the shared crucible of war and exile as Jewish émigrés. This shared context helps illuminate the significance of their intellectual contributions by uncovering the webs of meaning in which their work was suspended.
History
Keywords: Europe; European economic history; Jewish émigrés; KISCH; Guido; LOPEZ; Robert; OELSNER; Toni; POSTAN; Michael; biographical; economic history; historical literature; identity (philosophical concept); immigrants; intellectuals; medieval economic history; research

The peaceful conspiracy: bond markets and international relations during the Pax Britannica - Flandreau, Marc; Flores, Juan H. (International Organization, 2012)
This article provides foundations to K. Polanyi's famed argument that monopoly power in the global capital market served as an instrument of peace during the Pax Britannica (1815-1914). We focus on the role of intermediaries and certification. We show that when information and enforcement are imperfect, there is scope for the endogenous emergence of 'prestigious' intermediaries who enjoy a monopoly position and as a result, control government actions. They can implement conditional lending: they subject the distribution of credit to the adoption of peaceful policies. Prestigious intermediaries act that way because of their concern with maintaining an unblemished track record when wars increased risks of default. Our analysis, which brings together insights from different disciplines, provides a significant extension to, and departure from, recent research on how countries accumulate reputational capital.
History
Keywords: Pax-Britannica; United Kingdom; bond markets; economic history; global capital market (1815-1914); international relations

Embedding Markets in Temporal Structures: A Challenge to Economic Sociology and History - Eisenberg, Christiane (Die Einbettung von Märkten in temporalen Strukturen: Eine Herausforderung für Wirtschaftssoziologie und Geschichte., 2011)
The essay examines from a historian's point of view the approaches to the analysis of market exchange in new economic sociology and explores in which way sociology and history can cooperate in embedding markets in temporal structures. In a first step the author sharply criticises the favourable reception given to Karl Polanyi's work "The Great Transformation" in the field of new economic sociology. In particular she discusses the narrowing of research perspectives and its negative side effects on the sociology of markets. There then follows a second step: in order to find a linking point for interdisciplinary cooperation, beginning with the current state of historical research, the author makes several considerations on the significance of temporal structures and the time factor in general in analysing markets and market societies.
History
Keywords: Continental Europe; England; Great Britain; economic history; economic sociology; history - methodology; interdisciplinary approach to knowledge; interdisciplinary research; longue durée; market society; socioeconomics; time structures

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
History; Economics
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

À propos de « ceux qui sont en dehors de la société ». L'indigent et l'assistance publique au Québec dans la première moitié du XXe siècle - Petitclerc, Martin (Revue d'histoire de L'Amerique francaise. automne2011/hiver2012, Vol. 65 Issue 2/3, p227-256. 30p., 2011)
The “ Loi établissant le service de l'assistance publique" (Public Welfare Act) sparked considerable controversy after its adoption in 1921 .The Act provided for provincial and municipal grants to private and religious institutions providing shelter to the poor and destitute. Led by Henri Bourassa, among others, the debate concerned the problem of state intervention in an area traditionally conceived of as the responsibility of the Church. In contradiction to Bourassa's theories, most historians analyzed the A c t through the rubric o f modernization as a necessary affirmation of State prerogatives in the area of social protection. In this article, we argue that this Act is an attempt (largely successful) to consolidate a form of liberal governmentality based on, since the 19th century, what Karl Polanyi termed “the figure of the pauper" According to this perspective, the 1921 A c t is not a significant stage in the age-old struggle between Church and State, but rather a time of reform in liberal politics in regards to "the indigent 'The latter leggally defined as unable to work and without family support, and therefore “ outside of society," an expression of the day, allowed justifying the development o f a private/public system of charitable assistance against the project o f social policies founded on a universal conception of social rights. The article presents this dynamic through an analysis of the contentious issue of the rights of indigents to public assistance. (English)
History
Keywords: BOURASSA; Henri; 1868-1952; Canada; Quebec; church & state - Canada; liberalism - Canada; poor people - Canada; poor people - government policy; poor people - services for - history; public welfare - Canada - history

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
History; Economics
Keywords: classical Greek economy; economic history; embeddedness

Polanyi in the United States: Peter Drucker, Karl Polanyi, and the Midcentury Critique of Economic Society - Immerwahr, Daniel (Journal of the History of Ideas, 2009)
Abstract:This essay explores the connections between Karl Polanyi's The Great Transformation (1944) and midcentury social theory in the United States. It argues that Polanyi shared with his U.S. colleagues a critique of market society. In particular, Polanyi's work bears close resemblance to the early thought of management theorist Peter Drucker, with whom Polanyi lived while writing his celebrated book. By comparing Polanyi to his contemporaries who advanced similar ideas, one gains a clearer sense of the particularities of Polanyi's project and of the fairly widespread movement in the United States to reject economistic thinking.
History
Keywords: DRUCKER; Peter; history; social theory

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
History; Sociology
Keywords: biography; essence of fascism

Hititlerde Devlet Gelirleri, Depolama ve Yeniden Dağıtım - Reyhan, Esma (The Revenues of Hittite State, Storage and Redistribution., 2009)
The economic system of Hittite Kingdom shows parallelism with a description of Polanyi about redistribution system, as "Tributes firstly flow to the capital of an emperor, and then from there to the provinces". This system completely depended upon the social hierarchy. Tributes firstly flow to the capital of an emperor, and then from there to the provinces. This essay examines the tax collection system of the Hittite Empire, especially the aspect of redistribution of the taxes from the capital to the provinces. As the taxes flow firstly into Hattuşa and later to the provinces, we are trying to draw the conceptional frame of the "redistribution in centralized system". This will also make it possible to consider the management structure of the Hittite Empire as well. (English)
History; Archaeology
Keywords: Hattuşa/Boğazköy; Hattuša/Boğazköy; Hitit Devleti; Hitit Ekonomik Sistemi; Hitit Kanunları; Hitit Ritüel Metinleri; Hitit Çiviyazılı Tabletler; Hittite Cuneiform Tablets; Hittite Economic System; Hittite Laws; Hittite Ritual Texts; Hittite State; Hittites; capital cities; dominance (psychology); kings & rulers; storage; tax administration & procedure; tax collection; tax penalties; warehouses

Karl Polanyi : une voix du siècle passé, Abstract - Cangiani, Michele (Revue du MAUSS, 2009)
RésuméSituer Karl Polanyi dans son temps et par rapport aux grandes théories sociales du passé, y compris celle de Marx, nous permet de mieux comprendre les problèmes du temps présent. C’est de ce point de vue que l’article cherche à mettre brièvement en relief quelques aspects de la contribution de Polanyi à la connaissance historique, à la critique de la science économique et à la théorie politique., To consider Karl Polanyi’s thought in relation to his time and to great social theories of the past, Marx’s theory to begin with, can improve our understanding of problems of current times. This is the starting point of this article’s attempt to synthetically focus some aspects of Polanyi’s contribution to historical knowledge and political theory, and of his critique of economics.
History
Keywords: political theory

Karl Polanyi for Historians: An Alternative Economic Narrative - Knowles, Rob; Owen, John R. (The European Legacy, 2008)
The purpose of this essay is to provide the historian with a generic understanding of the term economy by examining some aspects of the work of the Hungarian “economic historian” Karl Polanyi (1886–1964). It does not seek to explain Polanyi's economic ideas to economists nor does it seek to locate his ideas within the discourses of the academic discipline of economics; there is abundant academic literature which carries out those tasks. This essay is intended to help fill a void in the historical understanding, especially the modern historical understanding, of the term economy, and of how the characteristics associated with it are generally understood. Yet, in reality, it is the neoclassical paradigm of economics which is typically and uncritically taken to be the touchstone for understanding the economy. This circumstance is problematic, however, when referring to the economy of societies earlier than the late nineteenth century or of societies whose culture differs radically from that of the advanced capitalist “west.” Polanyi's insights may help historians avoid the risk of either distorting or anachronistically misunderstanding the economy of such societies.
History
Keywords: economic history; economic theory; history

Weber, Polanyi, and Finley - Tompkins, Daniel P. (History and Theory, 2008)
KM: a review article on Nafissi's book.
History
Keywords: WEBER; Max; 1864-1920; biography; review

Karl Polanyi y el Problema De Los Mercados - Colombo, Octavio (Studia historica., 2008)
The purpose of this work is to analyze the Karl Polanyi’s conceptions about the pre-capitalist-markets, especially his revision of the categories of trade, money and market. In first place, we present a critical examination of the fundamental ideas of The Great Transformation, where his later reflections about pre-industrial societies are ground. Using some basic categories of the critique of political economy, we treat to show certain methodological and conceptual limits of his proposal. Then, we analyze the Polanyi’s ideas related to the features of pre-capitalist markets. We conclude that, even when the polanyian categories and reasoning need a deep revision, his merit is to propose a really historical approach about the markets; approach that until now has not received a suitable attention.
History
Keywords: Great Transformation; The (Book); critique; great transformation; pre-capitalist markets; preindustrial society

Karl Polanyi et la séparation institutionnelle entre politique et économie - Buğra, Ayşe (Raisons politiques, 2005)
This article explores Karl Polanyi’s analysis of the institutional separation of politic and the economy in the context of the 19th century market economy. The contribution his analysis could make to the quest for viable alternatives to the contemporary neo-liberal international order depends on how we construe two key concepts in his work, “disembeddedness” and “countermovement”. In this regard the author suggests that: 1) In Polanyi’s work the disembedded economy appears not as a sociological reality but as a political project, and 2) Polanyi’s analysis of the countermovement does not justify all types of resistance to the market economy as humane and politically acceptable.
Economics; History
Keywords: institutional separation

Le port de commerce : un concept en débat - Graslin, Laetitia; Maucourant, Jérôme (Topoi, 2005)
Economics; History
Keywords: Dahomey and the Slave Trade; port of commerce

Meat for the Multitudes: Market Culture in Paris, New York City, and Mexico City over the Long Nineteenth Century - Horowitz, Roger; Pilcher, Jeffrey M.; Watts, Sydney (American Historical Review, 2004)
Examines an earlier period of oscillation between state intervention and market liberalization in the meat trades of Paris, France New York City, and Mexico City, Mexico. Explanation on market culture; Argument of economic historian Karl Polanyi on the modern capitalist system and market rationality; Discussion on the rules governing the relationship between civil society and state power in the meat trade.
History
Keywords: Mexico; Mexico City; New York; Paris (France); civil society; intervention (federal government); liberalism; market liberalization; meat industry; state intervention

Debt Peonage in Granada, Nicaragua, 1870-1930: Labor in a Noncapitalist Transition - Dore, Elizabeth (Hispanic American Historical Review, 2003)
Revisits the debt peonage debate, central to understanding Latin American transitions to capitalism, particularly in Diormo, Granada, Nicaragua. Differences between capitalist and noncapitalist societies according to Karl Polanyi and Robert Brenner; Land peasantry in Diriomo; Legislation enacted to compel peasants to work in plantation agriculture.
History
Keywords: BRENNER; Robert; 1943-; Nicaragua; capitalism; debates and debating; history; labor laws & legislation; labour laws & legislation; peasants

The Forgotten Institution - Cangiani, Michele (International Review of Sociology, 2003)
Presents views of scholar Karl Polanyi on economic integration. Views of Polanyi on modern capitalist society; Distinction between external, local and internal markets by Polanyi. The three forms of economic integration include reciprocity, redistribution, and exchange. The article discusses Polyani's book "The Great Transformation," the development of market economies, the self-regulating market, some of the writings of Max Weber, big businesses, the efficiency of the market system, and social engineering.
History
Keywords: Great Transformation; The (Book); WEBER; Max; 1864-1920; big business; capitalism; international economic integration; social engineering

State Formation, Habitus, and National Character: Elias, Bourdieu, Polanyi, and Gellner and the Case of Asylum Seekers in Ireland - Loyal, Steven; Quilley, Stephen (Historical Social Research, 2020)
Synthesizing material derived from Norbert Elias, Pierre Bourdieu, Karl Polanyi, Max Weber, Benedict Anderson and Ernest Gellner, in Part I the concept of “national character” is delineated as a special case of “habitus” relating to the socio-spatial scale of the nation state. In relation to problems of state-formation, national character is shown to be a figurational and co-developmental function of the system of nation-states in which patterns of mutual identification and “imagined community” involve both the coercive codification and internalization of particular national narratives and origin myths which define “people like us” in terms of a symbolic family; and also, in relation to competing nation-states, the projection and internalization of national group charisma and shame. In Part II, these ideas are applied to the pattern of state formation in Ireland and the recent history of the reception, cultural accommodation, and treatment of asylum seekers.
Keywords: BOURDIEU; Pierre; 1930-2002; ELIAS; Norbert; Ireland; Irishman; Kultur; Sozialpsychologie; Staatenbildung; culture; figuration; habits; habitus; nation; national identity; national stereotype; nationale Identität; nationales Stereotyp; social psychology; state formation

'Freedom in a Complex Society': The Relevance of Karl Polanyi's Political Philosophy in the Neoliberal Age - Cangiani, Michele (International Journal of Political Economy, 2012)
Karl Polanyi's demanding vision of freedom and democracy seems far from the reality of our times and current ideologies. However, a deeper analysis reveals the ability of his political philosophy not only to find a solution of the paradox of liberty in spite of social constraints, indeed through social institutions, but also to answer the most important practical question with which we are confronted: that of improving, as Polanyi says, "our chances of survival." The conception synthetically expounded in the last pages of The Great Transformation can be better clarified through some of Polanyi's recently published manuscripts of the interwar period. A reference is also to be made to Karl Marx in the first place but also to other more recent authors.
History; Political Science
Keywords: capitalist systems; elections; freedom in a complex society; history of economic thought; legislatures; lobbying; political philosophy; political processes; rent-seeking; voting behavior